Glazed wall tile and lime mortars in the city of Oporto (1850 - 1920). Symptoms and causes of degradation - L. M. FERREIRA (2008)
The anomalies affecting the system ceramic glazed wall tile, mortar and hydrophobic layer on granite resistant masonry in the Oporto's ancient buildings constructed between 1850 and 1920 are important not only for the good individual functioning of each element but also as they affect the whole system and place people and properties at risk, besides an aesthetic degradation of the built urban spot surfaces. A synthesis of the most frequent individual anomalies of these systems and their causes will be carried through. For a better understanding different tables systemize the causes by typology of the anomalies, isolating each part of the above-mentioned system. In conclusion the relations established between the different elements will be identified.